Terjemahan Struktur Informasi Bahasa Arab dan Bahasa Indonesia: Studi Kasus Produk Terjemahan Aforisme Al-Hikam - Anis, Muhammad Yunus (Kementerian Sekretariat Negara Republik Indonesia, 2021)
This study examined the translation of the information structure in Arabic into Indonesian. The transfer of information structure in the two typologically different languages ​​will cause various kinds of problems. Arabic is a flexion type, while Indonesian is agglutinative type. This study investigated two main things: how is the form of the information structure of Themes and Rhemes in Arabic (SL) and Indonesian (TL), then how the information structure is developed in a pattern of development of themes (thematic progression), whether there will be a shift in translation from Source Language (Arabic) to Target language (Indonesian). The research method used in the study is divided into three main stages, the first stage of data collection using the observation method of linguistic units found in Al-Hikam aphorisms (Arabic - Indonesian). The second stage of data analysis using the Spradley model, namely: domain analysis, taxonomic analysis, componential analysis, and analysis of cultural themes. The third stage is reporting the results using a narrative form which is expected to be the basis for recommendations for translators to be more careful and pay attention to the details of the information structure in the translation process. Keywords: Al-Hikam Aphorism, Arabic-Indonesian Translation, Information Structure, Theme-Rheme.